Cho dãy tỉ số bằng nhau [tex]\frac{2bz-3cy}{a}=\frac{3cx-az}{2b}=\frac{ay-2bx}{3c}[/tex]
Chứng minh: [tex]\frac{x}{a}=\frac{y}{2b}=\frac{z}{3c}[/tex]
Theo đề ta có :
[tex]\frac{2bz-3cy}{a}=\frac{3cx-az}{2b}=\frac{ay-2bx}{3c}[/tex]
=>[tex]\frac{2abz+3acy}{a^{2}}=\frac{6bcx+2abz}{4b^{2}}=\frac{3acy-6bcx}{9c^{2}}[/tex]
Áp dụng t/c của dãy tỉ số = nhau , ta có:
Ta suy ra được : [tex]\frac{0}{a^{2}+b^{2}+c^{2}}=0[/tex]
=>2bz=3cy =>[tex]\frac{z}{3c}=\frac{y}{2b} (1)[/tex]
=>3cx=ax => [tex]\frac{x}{a}=\frac{z}{3c} (2)[/tex]
=>ay=2bx => [tex]\frac{x}{a}=\frac{y}{2b} (3)[/tex]
Từ (1)(2)(3) =>[tex]\frac{x}{a}=\frac{y}{2b}=\frac{z}{3c}[/tex]
Vậy [tex]\frac{x}{a}=\frac{y}{2b}=\frac{z}{3c}[/tex]